Hospital Dentistry in COVID-19 times - Rebeca Ester dos Santos Boaventura Silva; Jesse Oliveira Alves; Marley Caroline Ramos Alcantara; Júlia Ramos Barbosa; Alessandra Laís Pinho Valente Pires; Marília de Matos Amorim (Universidade Federal do Rio Grande do Sul. Faculdade de Odontologia, 2021)
The COVID-19 pandemic led the world's population to rethink all forms of human relationships. Like other areas of health, Hospital Dentistry has also undergone adaptations to the current situation. Aim: To present the main changes that have occurred in the role of dentists in the hospital environment as a result of COVID-19. Literature review: Dental practice is based on the use of instruments that promote the emission of aerosols. In view of the increased risk or dissemination of SARS-CoV-2 during hospital dental procedures, oral health professionals must be properly dressed and respect all the protocols established for this period. Discussion: After reducing residual saliva, it is recommended to use 1.0% hydrogen peroxide, before 0.12% or 0.2% chlorhexidine, without alcohol, and proceed with oral lubrication. The performance of oral hygiene in tracheostomized patients to prevent VAP in the hospital environment should be maintained in order to avoid new cases of infection by microorganisms other than SARS-CoV-2. Conclusion: Biosafety during dental practices should never be neglected, especially in the current pandemic scenario.